Happiness Behind the Scenes: Associations between Heuristic Happiness and Related Dimensions in Skin Diseases - Johanna Weis; Hannah Wecker; Alexander Arnold; Barbara Schuster; Stefanie Ziehfreund; Linda Tizek; Sonja Mittag; Tilo Biedermann; Alexander Zink (Medical Journals Sweden, 2023)
Positive health approaches, such as happiness, are largely unexplored in medicine, including dermatology. Taking into consideration the various happiness measures, the aims of this cross-sectional study were to assess this concept using a 1-item heuristic happiness question and its related dimensions (Satisfaction with Life, Positive and Negative Affect, Quality of Life, and Compound Psychological Capital) in outpatients with different skin diseases between December 2019 and June 2020, and to examine the link between these dimensions. Overall, 414 dermatological patients were included: 67 with psoriasis, 84 atopic eczema, 10 mastocytosis, 19 nummular eczema, 84 malignant melanoma and 150 keratinocyte carcinoma. Comparing the skin diseases, differences were observed for heuristic happiness, Positive Affect, and some domains of Quality of Life and Compound Psychological Capital. Analysing the relationship between heuristic happiness and other happiness measures, the data revealed moderate to strong correlations (r = 0.30-0.46, p< 0.001) and variations in the understanding of happiness between the skin diseases. Overall, the most important facet of happiness was Hope as a domain of Compound Psychological Capital. This study emphasizes the individual definition of heuristic happiness in patients with skin diseases. A 1-item heuristic approach may be a simple and practical method to assess the complexity and individuality of happiness.